2010
DOI: 10.1111/j.1471-0307.2010.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the physico‐chemical properties of low‐cholesterol ghee with standard ghee from cow and buffalo creams

Abstract: Low‐cholesterol ghee with 90% less cholesterol was prepared using β‐cyclodextrin. The physico‐chemical properties such as Reichert‐Meissl (RM) value, Polenske value, Butyro‐refractometer (BR) reading at 40°C, Iodine value and free fatty acids (FFA) as oleic acid in cow standard ghee and the corresponding low‐cholesterol ghee remained almost unaltered. A similar trend was also observed in buffalo ghee. Fat soluble vitamins (β‐carotene, A and E) in both cow and buffalo low‐cholesterol ghee were very similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…Table 3 shows the individual phytosterol composition of native and blended fat samples. Kumar et al (2010) have reported that the cholesterol content of butterfat, which is around 3190 mg/kg. The result shows that the sterol part of butterfat comprises only cholesterol (2550 mg/kg).…”
Section: Thermal Behaviours Of the Butterfat And Prpol Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 shows the individual phytosterol composition of native and blended fat samples. Kumar et al (2010) have reported that the cholesterol content of butterfat, which is around 3190 mg/kg. The result shows that the sterol part of butterfat comprises only cholesterol (2550 mg/kg).…”
Section: Thermal Behaviours Of the Butterfat And Prpol Blendsmentioning
confidence: 99%
“…In addition, studies have reported a positive correlation between serum cholesterol level and dietary intake of cholesterol. The several methods have been adopted to reduce the levels of cholesterol in ghee (Kumar et al 2010;El-Aziz et al 2013). Rodrigues and Gioielli (2003) have blended butter oil with corn oil and modified chemical interesterification to get the improved physical and nutritional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a process was developed to remove cholesterol from ghee, the most popular dairy product in India, and a product known as low‐cholesterol ghee was prepared (Kumar et al . ). This product meets all the quality standards of ghee and have storage stability and granulation behaviour parallel to regular ghee (Kumar et al .…”
Section: Introductionmentioning
confidence: 97%
“…This product meets all the quality standards of ghee and have storage stability and granulation behaviour parallel to regular ghee (Kumar et al . ; Meghwal et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…Ghee contributes significantly towards nourishment of people of all age groups. It is a good source of fat-soluble vitamins (A, D, E and K) and essential fatty acids (Chand et al 1986;Rangappa and Achaya 1974;Kumar et al 2010). Along with these advantages, concerns about its high cholesterol content (0.2-0.4 %) and its relation with cardiovascular diseases is also increasing.…”
Section: Introductionmentioning
confidence: 99%